Environmental impacts of chocolate production and consumption in the UK. (April 2018) - Konstantas, Antonios; Jeswani, Harish K.; Stamford, Laurence; Azapagic, Adisa
Abstract: This study evaluates life cycle environmental impacts associated with chocolate products made and consumed in the UK. The paper focuses on three representative chocolate products occupying 90% of the market: 'moulded chocolate', 'chocolate countlines' and 'chocolates in bag'. The impacts were estimated using life cycle assessment (LCA) as a tool and following the ReCiPe impact assessment method. The water footprint was also considered. For example, the global warming potential ranges between 2.91 and 4.15 kg CO2 eq., primary energy demand from 30 to 41 MJ and the water footprint, including water stress, from 31 to 63 l per kilogram of chocolate. The raw materials are the major hotspot across all impact categories for all three product types, followed by the chocolate production process and packaging. The raw material impacts are mainly due to milk powder, cocoa derivatives, sugar and palm oil. The sensitivity analysis shows that the results for global warming potential are sensitive to land-use change (LUC) associated with cocoa production, increasing the impact of the chocolate products by three to four times if LUC is involved. The improvement opportunities targeting the key contributing stages suggest that GWP of chocolates could be reduced by 14%–19%. Chocolate countlines have the highest contribution to the total impacts at the UK level (37%–43%), followed by chocolates in bag (28%–33%). Moulded chocolates and other chocolate confectionary make up the rest of the impacts, with a roughly equal share each. Chocolate consumption in the UK contributes 4.7% to the primary energy consumption and 2.4% to the GHG emissions from the whole food and drink sector. The results of this work will be of interest to policy makers, chocolate producers and consumers, helping them to make more informed decisions towards sustainable production and consumption of chocolate products. Graphical abstract: Unlabelled Image Highlights: Global warming potential (GWP) of chocolate ranges from 2.9–4.2 kg CO2  eq./kg. Around 10, 000 l of water is needed to produce a kilogram of chocolate. Land-use change associated with cocoa production increases total GWP by 3–4 times. GWP could be reduced by 14%–19% through various improvement options considered.